On differentiation and harmonic numbers - Mortenson, Eric (Utilitas Mathematica, 2009)
In a paper of Andrews and Uchimura [AU], it is shown how differentiation applied to hypergeometric identities produces formulas for harmonic and q-harmonic numbers. Here we recall two binomial coefficient sums that appear in [M], and reprove them using the techniques of (AU).